Understanding The Role of Mass Media in Shaping Female Educational Attainment in Somalia - Alin, Abdirahman Osman; Abdillahi, Asia Abdirahman (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2025)
This study investigates the association between media exposure and educational attainment among women in Somalia, utilizing nationally representative data from the 2020 Somali Health and Demographic Survey. Drawing on a sample of 5,046 women aged 15–49, the study applies an Ordered Probit regression model selected for its superior fit (AIC; BIC) to assess how various forms of media engagement relate to levels of education attained. The authors found that 38.4% of women had no formal education, while only 5.7% had reached secondary or higher levels. Media exposure was generally low: 86.3% of women never read newspapers, 81.2% did not watch television, and 79.5% did not listen to the radio. Multivariate analysis indicates that women who watched television at least once a week were significantly more likely to attain higher education (β = 0.401, p 0.01), as were those who read newspapers weekly (β = 0.337, p 0.05). These highlight the positive role of media in educational advancement and point to persistent structural barriers that must be addressed to achieve equitable educational outcomes for women in Somalia.